Polar versus rectangular form. A complex number written as a + bi is in rectangular form. There is also the polar form. Represent z = a + bi on the Argand plane as an arrow. Then z is completely determined by knowing the angle θ it makes with the positive x-axis, and its modulus or length. Suppose the modulus of z = a + bi is r. Then by definition, cos θ = a/r, and sin θ = b/r. So a = r cos θ, b = r sin θ. Hence z = a + bi = r cos θ + r sin θ · i = r(cos θ + i · sin θ). Write cis θ = cos θ + i · sin θ. We call z = rcis θ the polar form of z. Here r = |z|, and θ is the argument of z, arg(z). Note that |cis θ| = 1. Example. Suppose z = √ 2cis π4 . Express z in rectangular form z = a + bi for a, b real. √ π z = 2cis 4 √ π π 2(cos + i · sin ) = 4 4 √ 1 1 = 2( √ + √ i) 2 2 = 1 + i. Example. Suppose |z| = 2 and arg(z) = 5π 6. So z = 2cis 5π 6 . Give z in rectangular form. Now π radians is 180 degrees. 5π · 180 = 150 degrees, or 180 − 30 degrees. So 5π radians is 6 6 π. Working in radians, 5π = π − 6 6 Hence π π cos(π + (− )) = − cos(− ) 6 6 π = − cos 6 √ 3 = − , 2 and likewise, π π sin(π + (− )) = − sin(− ) 6 6 π = sin 6 1 = . 2 √ 5π So cis 6 = − 23 + 1 2 i. Hence 5π 6 √ 1 3 = 2(− + i) 2 2 √ = − 3 + i. z = 2cis Example. Convert z = 1 + i to polar form z = r · cis θ. Now r = |z| = q 12 + 1 2 = √ 1+1= √ 2, so write z as z= √ 1 1 2( √ + √ i). 2 2 We must have cis θ = cos θ + i · sin θ 1 1 = √ + √ i, 2 2 so 1 1 cos θ = √ , sin θ = √ . 2 2 So θ = π/4 (or 45 degrees). So z= √ 2cis π . 4 √ 1 Example. Convert z = − 2 + 23 i to polar form. Again, |z| = q 1 + 3 = 1, so 4 4 √ 1 cis θ = − 2 + 23 i, and so √ 3 1 cos θ = − , sin θ = . 2 2 Now draw the situation! Must be in the second quadrant. Let δ be the angle made by z as measured from the negative x-axis. √ 1 and sin δ = 3 . Then cos δ = 2 2 So must have δ = π/3 (or 60 degrees). So θ = π − π/3 = 2π/3 radians, (or 180 − 60 = 120 degrees). So 2π 2π z = 1 · cis = cis . 3 3 What happens when we multiply together two complex numbers in polar form? Let z1 = r1cis θ1, z2 = r2cis θ2. Then z1z2 = (r1cis θ1)(r2cis θ2) = r1r2cis θ1cis θ2. On the worksheet, you are asked to prove that cis θ1 · cis θ2 = cis(θ1 + θ2), with the help of some trig identities. Hence z1z2 = r1r2cis(θ1 + θ2). This re-proves the fact proved earlier, that |z1z2| = r1r2 = |z1| · |z2|. We also have shown the following new fact: arg(z1z2) = arg(z1) + arg(z2). Example. Compute the product of 2 cis π/6 with 3 cis(−3π/2). (2 cis π/6)(3 cis(−3π/2)) = 6 cis (π/6 − 3π/2) π − 9π = 6 cis ( ) 6 −4π ). = 6 cis ( 3 Note that instead of cis θ, the notation eiθ is often used. The above formula involving cis then has a more intuitive form: eiθ1 eiθ2 = ei(θ1+θ2). We do not pursue this further now. Powers of complex numbers. We can now prove (by induction!) De Moivre’s formula: (r cis θ)n = rncis(nθ). Example. Find (−1 + √ 3i)8, in rectangular form. A key useful point here is that in general cis(θ + 2π) = cos(θ + 2π) + i sin(θ + 2π) = cos θ + i sin θ = cis θ. Let z = −1 + Then |z| = √ √ 3i. 1+3= √ 4 = 2, so √ 3 1 i), z = 2(− + 2 2 √ 3, so cos θ = − 1 , sin θ = 2 2 so in second quadrant. (Do a drawing.) We see that θ = π − π/3 = 2π/3. So z = 2cis 2π 3 . Hence (−1 + √ 2π 8 8 3i) = (2cis ) 3 2π ) by De Moivre 3 16π 8 2 cis 3 4π 28cis(4π + ) 3 4π 8 2 cis 3 π 28cis(π + ) 3 = 28cis 8( = = = = π π 8 = 2 (cos(π + ) + i · sin(π + )) 3 π π − i · sin ) 3 3 √ 1 3 = 28(− − i) 2 2 √ 7 = 2 (−1 − 3i) = 28(− cos √ = −128 − 128 3i. 3